Humoral and cellular immunity to SARS-COV-2 after vaccination with mRNA vaccines in PLWH with discordant immune response. Influence of the vaccine administered - López-Cortés, Luis F.; Saborido-Alconchel, Abraham; Trujillo-Rodríguez, María; Serna-Gallego, Ana; Llaves-Flores, Silvia; Muñoz-Muela, Esperanza; Pérez-Santos, María Jesús; Lozano, Carmen; Mejias-Trueba, Marta; Roca, Cristina; Espinosa, Nuria; Gutiérrez-Valencia, Alicia (Frontiers in Immunology, 2023)
Background. Data on SARS-CoV-2 mRNA vaccine immunogenicity in people with human immunodeficiency virus (PWH) with discordant immune response (DIR) are currently limited. Therefore, we compare immunogenicity of these vaccines in DIR and immunological responders (IR). Materials and Methods. Prospective cohort that enrolled 89 participants. Finally, 22 IR and 24 DIR were analyzed before vaccination (T0), one (T1), and six months (T2) after receiving BNT162b2 or mRNA-1273. Additionally, 10 IR and 16 DIR were evaluated after a third dose (T3). Anti-S-RBD IgG, neutralizing antibodies (nAb), neutralization activity, and specific memory B cells were quantified. Furthermore, specific CD4+ and CD8+ responses were determined by intracellular cytokine staining and polyfunctionality indexes (Pindex). Findings. At T1, all participants developed anti-S-RBD. 100% IR developed nAb compared to 83.3% DIR. Spike-specific B cells were detected in all IR and 21/24 DIR. Memory CD4+ T cells showed response in 5/9 IR and 7/9 DIR, mainly based on the expression of IFN-γ and TNF-α, with higher Pindex in DIR. Memory CD8+ T cells responded in only four participants in each group. At T2, anti-S-RBD and nAb titers were higher in DIR than IR. In both groups, there was an increase in specific B memory cells, higher in DIR. Six IR and five DIR maintained specific memory CD4+ response. Memory CD8+ response was preserved in IR but was lost in DIR. In a multivariate linear regression analysis, receiving mRNA-1273 instead of BNT162b2 played a prominent role in the results. Conclusions. Our results suggest that PWH with DIR can mount an immune response similar to those with higher CD4+, provided they receive the mRNA-1273 vaccine instead of others less immunogenic.